Molecular Detection and Treatment of Trypanosomiosis in a Cat: A Case Report - Jafarsab; Mamatha, Gotakanapura Sanjeevamurthy; Kumar, Niteesh; Bijurkar, Rajeshwar Gangaram; Doddamane, Rathnamma (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Trypanosomosis is one of the most common and important haemoprotozoan disease that affects humans and animals including cats (Mohammed et al., 2022). The aetiological agent for trypanosomiosis in cats is T. evansi and T. brucei (Priyowidodo et al., 2023). The disease has wide distribution in Africa, Asia, and Latin America (Da Silva et al., 2010) and mainly transmitted mechanically by biting flies such as Tabanus, Stomoxys and triatomids bugs or by feeding on infected meat (Sivajothi and Sudhakara Reddy, 2017; Mohammed et al., 2022). Infected cats show clinical signs such as anorexia, diarrhoea, decrease in weight, progressive anaemia, lethargy, lymphadenopathy, hyperthermia, corneal opacity, edema around the eyes and in-coordination (Da Silva et al., 2011: Sivajothi and Sudhakara Reddy, 2017: Priyowidodo et al., 2023). The rapid diagnosis of trypanosomosis in animals is commonly attempted by examination of wet mount smears, and blood smears stained with Romanowsky stains such as Giemsa stain. The polymerase chain reaction (PCR) technique can be performed for further confirmatory diagnosis (Mohammed et al., 2022: Priyowidodo et al., 2023). However, there was a paucity of literature available on natural infection of feline trypanosomosis in the world (Sivajothi and Sudhakara Reddy, 2017), Hence, the present case study on trypanosomosis in cat and its successful treatment in Bidar district, Karnataka, India is reported.